Exon 10 Prolactin Receptor Gene Polymorphism in Surti and Jaffarabadi Buffaloes by PCR-RFLP - Devkatte, Savita (Indian Journal of Dairy Science, 2021)
The present study was undertaken with the objectives to amplify Prolactin Receptor (PRLR) gene exon 10 region and to study PRLR gene polymorphism using PCR-RFLP in Surti and Jaffarabadi buffaloes. Blood samples from 50 Surti and Jaffarabadi buffaloes each were collected followed by DNA was extracted by phenol: chloroform method. Oligo primers specific to bovine PRLR loci were custom synthesized at Eurofins and utilized in the present experiment. Â Exon 10 region of PRLR gene resulted in 168 bp product. Restriction digestion of 168 bp fragment of PRLR gene using SmlI, revealed PCR products with a single band of GG genotype. The frequency of genotype GG and gene G were observed 1.0 each for both Surti and Jaffarabadi buffalo respectively. Both the population of buffaloes were found to be in genetic equilibrium for PRLR gene of exon 10 locus indicating that monomorphism at these loci may be a species characteristic of buffalo.